Diagnostic Performance of PI-RADS v2.1 for Clinically Significant Prostate Cancer in Indonesian Patients Undergoing MRI Fusion Prostate Biopsy - Nyoman Aditya Sindunata; Vera Nevyta Tarigan; Patricia Jorisal; Bachtiar Murtala; Marto Sugiono; Veli Sungono (Medicinus, 2026)
Background: Prostate cancer is the second most common malignancy among men and one of the leading causes of cancer-related death. MRI evaluation using prostate imaging and data system (PI-RADS) v2.1 is widely applied to detect clinically significant prostate cancer (csPCa). However, data on its diagnostic performance in Indonesian population remain limited.   Methods: An analytical observational study with retrospective cross-sectional design was conducted on patients with PI-RADS category 3-5 who underwent MRI fusion prostate biopsy at Siloam Hospitals Kebon Jeruk between 2021 and 2025. Sensitivity, specificity, predictive values, and accuracy of PI-RADS v2.1 were evaluated against histopathological findings. Statistical analyses include Chi-Square and Mann-Whitney U test.   Result: A total of 75 patients were included, with a median age of 71 years (range: 49-84). The csPCa detection rates for each PI-RADS category were 14.29% for PI-RADS 3, 48.28% for PI-RADS 4 and 89.74% for PI-RADS 5. Histopathology confirmed csPCa in 50 patients (66.67%) and non-csPCa or benign lesions in 25 patients. The sensitivity of PI-RADS v2.1 at a cutoff ≥4 was 98% (95% CI 89.35–99.95), specificity 24% (95% CI 9.36–45.13), positive predictive value (PPV) 72.06%, negative predictive value (NPV) 85.71%, and overall accuracy 73.33% (95% CI 61.86–82.89). Bivariate analysis showed that older age, higher PSA, larger lesion size, PSA density ≥0.15 ng/ml2, and PIRADS 4/5 category were significantly associated with csPCa.   Conclusions: PI-RADS v2.1 demonstrates very high sensitivity and good NPV for excluding csPCa but has low specificity, resulting in moderate overall accuracy (73.33%).